PROSES PEMBELAJARAN FIQIH DI KELAS 1 MI NU NAHDLATUL ATHFAL - Khalimatul A'isah A'isah (Abtadi : Jurnal Pendidikan Dasar, 2022)
This study aims to determine the fiqh learning process in grade 1 MI NU Nahdlatul Athfal in 2022/2023. This research is a qualitative research. The type of research used in this research is field research, namely research directly into the field to obtain information related to the fiqh learning process in grade 1 MI NU Nahdlatul Athfal in 2022/2023. The techniques used for data collection are using observation, interviews, and documentation. Data analysis techniques consist of data collection, data reduction, data presentation, and conclusions. From the results of this study, it can be concluded that the fiqh learning process in grade 1 MI NU Nahdlatul Athfal Puyoh Village, Dawe District, Kudus Regency, has been carried out clearly and smoothly starting from the planning, implementation, and evaluation stages. In the learning process, problems were found, including the learning method still using lectures, teachers were not optimal in class mastery, students did not pay attention to learning, learning materials had not been delivered optimally, learning media that only used whiteboards and books. Solutions to overcome these problems include; Teachers should use more varied learning methods; The teacher must be able to master the hearts of the students; Students who do not pay attention, should the teacher give educational punishment; Teachers should use fun learning media; Teachers must add facilities that are used as support in learning in the classroom; Teachers invite students to make diversity as cheap props (APM) that can support fiqh learning; Teachers are also more initiative to always take advantage of advanced technology.